Strengthening The Character Trait of Peacefulness through Habitual Communication Practice of ‘3S’ (Smiling, Greeting, Saying Hello) at Early Childhood Education and Care - Haq, Muhammad Dhiyaul; Muslimin, Khoirul; Subaidi, Subaidi; Kalupae, Abdulaziz (THUFULA, 2024)
Abstract: This study aims to describe the reinforcement of the character trait of peacefulness in students through the habitual communication practice of the "3S" approach ("senyum," "salam," and "sapa") or smiling, greeting, saying hello at Taman Todda Qur'ani Early Childhood Education (PAUD) School in Jepara. The research employs a qualitative approach, with the study conducted at Taman Todda Qur'ani PAUD School in Jepara. The primary data sources for this research include the principal and teachers within the school environment. Data collection techniques involve interviews, observations, and documentation related to reinforcing the character of peacefulness through the habitual communication practice of the "3S" approach. The data analysis process involves data reduction, data presentation, and conclusion. The findings indicate that the habitual communication practice of "3S" effectively strengthens the students' character of peacefulness in the early childhood education environment of Taman Todda Qur'ani PAUD. Indicators of peaceful character include speaking politely to others when resolving conflicts, avoiding physical force, and demonstrating mutual love and care. The character of peacefulness is an attitude that fosters a sense of calm, safety, and comfort within society.